Planning with a gender lens: A gender analysis of pandemic preparedness plans from eight countries in Africa (2023)
ABSTRACT: Background: Health planning and priority setting with a gender lens can help to anticipate and mitigate vulnerabilities that women and girls may experience in health systems, which is especially relevant during health emergencies. This study examined how gender considerations were accounted for in COVID-19 pandemic response planning in a subset of countries in Africa. Methods: Multi-country document review of national pandemic response plans (published before July 2020 and as of March 2022) from Ethiopia, Ghana, Kenya, Nigeria, Rwanda, South Africa, Uganda, and Zambia, supplemented with secondary data on gender representation on planning committees. A gender analysis framework informed the study design and the Morgan et al. matrix guided data extraction and analysis. Results: All plans reflected implicit and explicit considerations of the impacts of the pandemic responses on women and girls. Through a gender lens, the implicit considerations focused on ensuring safety and protections (e.g., training, access to personal protective equipment) for community and facility-based health care workers and broad engagement of the community in risk communication. The explicit gender considerations, reflected in a minority of plans, focused on addressing gender-based violence and providing access to essential services (e.g., sexual and reproductive health care, psychosocial supports), products (e.g., menstrual hygiene products) and social protection measures. Women were underrepresented on the COVID-19 planning committees in all countries. Conclusions: The plans reflected varying national efforts to develop pandemic responses that anticipated and reflected unique vulnerabilities faced by women, though subsequent plans reflected further consideration of gender-relevant impacts compared to initial plans. Embedding a gender lens in emergency preparedness planning furthers equity and could support anticipation and timely mitigation of negative outcomes for women and girls who are often further marginalized during health emergencies. Keywords: COVID-19; Equity; Gender; Gender analysis; Pandemic preparedness planning.